A Little Bit Pregnant? Productive Ambiguity and Fertility Research. Issue 2 (27th April 2021) - Bell, Suzanne O.; Fissell, Mary E.
Abstract: Fertility researchers rely upon a simple binary: pregnant versus not pregnant. However, this conceptualization does not capture many women's experiences, both historically and in numerous settings today. We suggest that pregnancy status may be a much more ambiguous state, and that such ambiguity is often productive for women. Building a culturally sensitive understanding of what we are calling "productive ambiguity" can foster more rigorous studies of fertility that better capture potential pregnancy and the range of post‐coital fertility‐inhibiting actions women take, both intentionally and not. In this paper, we aim to: 1) describe the ambiguity that exists around pregnancy; 2) explain the ways in which this ambiguity is productive for women; 3) analyze two concrete examples of such ambiguity in practice: the case of menstrual regulation and the unexpected conceptual overlaps between contraception and early abortion in a variety of settings, and finally; 4) suggest ways that this more nuanced understanding might inform fertility research, including abortion measurement research. We combine recent qualitative and quantitative data with historical sources to analyze the cultural logics and power dynamics of this ambiguity.